L'insertion professionnelle des finissantes et des finissants du Conservatoire de musique du Québec - Perron, Denis; Cloutier, Renee (Canadian Journal of Higher Education, 1997)
Although the Conservatoire de musique du Québec (CMQ) has existed for half a century, to date very little information has been compiled on the origins of its students or on how its graduates have fared. We have thus produced a data bank on this clientele, covering students who graduated from the CMQ between 1988 and 1991, and used it to determine how their careers have progressed since this time. In order to better comprehend the factors influencing the students' integration into the labour market, which is the aim of the article, we have taken into account gender, family background, age at which musical training began, levels of schooling completed, main area of study, and the grades obtained from the institution. It would be interesting to determine whether a large proportion of these individuals pursued their musical training after graduating from the CMQ. We do know, however, that over 80% of employed CMQ graduates found jobs in a field related to their studies.